Evaluation of outcomes of lumbar interbody fusion for L4-L5 spondylolisthesis at ThaiBinh general Hospital (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: To evaluate the outcomes of lumbar interbody fusion surgery for L4-L5 spondylolisthesis at Thai Binh general hospital from January 2022 to January 2024. Method: A retrospective cross-sectional study was conducted among 68 patients suffered from L4 - L5 lumbar spondylolisthesis and had operated at the Neurospine Surgery Department in Thai Binh general hospital. Results: The median age of patients undergone lumbar interbody fusion was 49,5 ± 10 (years old). Gender ratio was 3 females per 1 male, the duration of disease detection was 38±18 (months). Postoperative outcomes verified that lumbar interbody fusion was the safe and effective surgery with short operation duration (123,9 ±13,2 minutes), 5,9% of intraoperative adverse incidents, 25% of short-term postoperative complications, 5,8% of long-term complications of the surgery. Good and satisfactory outcomes achieved 86 8% without any poor outcomes based on Macnab criteria. Conclusion: lumbar interbody fusion for L4-L5 spondylolisthesis is a safe and highly effective surgery.